IMPLEMENTASI METODE PICTURE AND PICTURE DALAM PEMBELAJARAN MENULIS TEKS PROSEDUR DI KELAS XI - Iis Royani Asyfa; Elis Mantalias; Reka Yuda Mahardika (IKIP Siliwangi, 2019)
This research is based on the ability of students to write, especially writing procedure texts that are still low. There are still many students who find it difficult to develop the results of their ideas. The related problem in this study is how is the description of student performance in the implementation of the picture and picture method in learning to write procedure texts? Is there a difference in the ability to write procedure texts before and after using the picture and picture method? The pre-experimental research method with the one group pre-test post-test design approach was used by the researcher by conducting the initial test before being given treatment so that the comparison of values before and after treatment was seen significantly. The researcher took a sample of 30 students in class XI. Data collection techniques were carried out by conducting the initial test (pretest) and the final test (posttest). Based on the test results that have been described, the average value before applied to the learning method is 51.87 and the average value after the learning method is applied is 77.97. Based on Software Statistics 22, the results of the normality test 0.15> 0.05 are declared a normal distribution, the results of the homogeneity test 0.066> 0.05 have homogeneous variances, and the results of the t-test sig (2-tailed) 0,000 <0.05 so the hypothesis is accepted. The conclusion in this study has been a change after given the method of picture and picture on learning to write procedure texts.